Synthesis and characterization of high-affinity 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene-labeled fluorescent ligands for human β-adrenoceptors - Baker, Jillian G.; Adams, Luke A.; Salchow, Karolina; Mistry, Shailesh N.; Middleton, Richard J.; Hill, Stephen J.; Kellam, Barrie (American Chemical Society, 2011)
The growing practice of exploiting noninvasive fluorescence-based techniques to study G protein-coupled receptor pharmacology at the single cell and single molecule level demands the availability of high-quality fluorescent ligands. To this end, this study evaluated a new series of red-emitting ligands for the human β-adrenoceptor family. Upon the basis of the orthosteric ligands propranolol, alprenolol, and pindolol, the synthesized linker-modified congeners were coupled to the commercially available fluorophore BODIPY 630/650-X. This yielded high-affinity β-adrenoceptor fluorescent ligands for both the propranolol and alprenolol derivatives; however, the pindolol-based products displayed lower affinity. A fluorescent diethylene glycol linked propranolol derivative (18a) had the highest affinity (log KD of -9.53 and -8.46 as an antagonist of functional β2- and β1-mediated responses, respectively). Imaging studies with this compound further confirmed that it can be employed to selectively label the human β2-adrenoceptor in single living cells, with receptor-associated binding prevented by preincubation with the nonfluorescent β2-selective antagonist 3-(isopropylamino)-1-[(7-methyl-4-indanyl)oxy]-butan-2-ol (ICI 118551) (J. Cardiovasc. Pharmacol. 1983, 5, 430-437.)